The Motive of Deception in the Work of S.Dovlatov - DOBROZRAKOVA, GALINA (Bulletin of Yerevan University H: Russian Philology, 2021)
The article is devoted to consider the motive of deception manifested in the works of Sergei Dovlatov on the levels of the author’s worldview (illusion), poetics (mystification, jokes, pseudodocumentaries), problematics (disclosure of the Soviet society’s falsity and doublethink ). The author uses materials from Soviet periodicals, which published Dovlatov, as well as the texts of the early story "the Man who never was", play-tale "the Man who never was. A play for primary school children with magic tricks, but no deception", the stories "Compromise" and "Reserve".